Alterations in Interleukin-1β and Interleukin-6 in mice inoculated through the oral routes using graded doses of p. Multocida type b: 2 and its lipopolysaccharide - Ali, Omar Suwaidan; Adamu, Lawan; Abdullah, Faez Firdaus Jesse; Ilyasu, Yusuf; Abba, Yusuf; Hamzah, Hazilawati; Mohd Lila, Mohd Azmi; Haron, Abd Wahid; Saad, Mohd Zamri (Science Publications, 2015)
The gram-negative bacterium Pasteurella multocida serotype B: 2 is an important veterinary and opportunistic human pathogen that causes deplorable welfare problems and colossal economic production losses in bovine and other animal species throughout the world. Pasteurella multocida type B: 2 and its LPS are associated with Haemorrhagic Septicaemia (HS) in mice as animal model. Sixty healthy Balb c mice were placed in twelve plastic cages each one containing five mice. The mice were divided into three major groups (A, B and C). Group A is the control group (n = 10) and these were inoculated with 0.4 mL of PBS pH 7.4 orally. The treatment groups (B; n = 25 and C; n = 25) were inoculated with P. multocida type B: 2 and lipopolysaccharide respectively. The mice in group B and C were further divided into five subgroups. The subgroups were designated based on the graded doses as B101, B103, B105, B107 and B109 for Pasteurella multocida and C101, C103, C105, C107 and C109 for LPS respectively. The mice were observed for 120 h post-inoculation. The concentration of IL-1Î² was significantly higher (p<0.001) in the B107 of P. multocida type B: 2 and C109 of LPS compared to the control group and the other treatment groups. The concentration of IL-6 was significantly higher (p<0.001) in the B103 cfu of P. multocida type B: 2 and C109 cfu of LPS compared to the control group and the other treatment groups. Interleukin-1Î² and interleukin-6 evaluated in this study were predominantly associated with HS in varying doses of 101, 103, 105, 107 and 109 in the whole cell and its LPS respectively. Therefore, the target of this study was to investigate on pro-inflammatory response in mice infected with graded doses of Pasteurella multocida serotype B: 2 and its LPS via the oral route of inoculation.